Forces of inertia - Abd Razak, Dzulkifli (2010)
"If India is to build a stable liberal democracy, if we are to empower the vast mass of the Indian public, if we want to give ourselves a more equitable and fair society, and if we want sustainable economic growth, then our university system desperately needs to be reformed."